The role of cytokines/chemokines in an aging skin immune microenvironment. (March 2023) - Lin, Zih-Chan; Hsu, Ching-Yun; Hwang, Erica; Wang, Pei-Wen; Fang, Jia-You
Abstract: Reversing or slowing down the skin aging process is one of the most intriguing areas of focus across the social and scientific communities around the world. While aging is considered a universal and inevitable natural process of physiological decline, the aging of the skin is the most apparent visual representation of an individual's health. Aging skin may be objectively defined by epidermal thinning; increased transepidermal water loss; decreased cutaneous barrier function; loss of elasticity, laxity, and textured appearance; and gradual deterioration of the epidermal immune environment. As the largest structure of the immune system and of the body as a whole, the skin is the most vulnerable barrier of defense against the environment. The skin reflects an individual's exposures, lifestyle habits, and overall health. From an immunological perspective, cytokines and chemokines act as a central character in the communicating of the immunity in skin aging. These cell signaling proteins serve as the intercellular communication link. This review aims to elucidate how cell-cell crosstalk through cytokines and chemokines, and the interplay between host cells, infiltrating immune cells, and exogenous factors contribute to the overall aging skin. Highlights: ● The skin is an active immune organ that combats attacks on the cutaneous microenvironment. ● Cytokines/chemokines act as a central role in the communicating of the immunity in skin aging. ● The interplay between host cells, immune cells, and exogenous factors contribute to the skin aging. ● This review describes the role of cytokines/chemokines in an aging skin immune microenvironment.